The Planet Already Turned Black: Colonization and Networked Subjectivities in Tade Thompson's Wormwood Trilogy. Issue 1 (1st March 2021) - Crowley, Dustin
Abstract : In its depiction of alien invaders colonizing human bodies in Nigeria, Tade Thompson's Wormwood Trilogy (2016–2019) at one level enacts a second contact narrative that recapitulates Africa's history with European imperialism and slavery. At the same time, the biotechnological instruments of this new alien invasion signal a deepened and expanded colonization, one that takes place at the scale of both the planetary and the cellular, and that threatens to ensnare and enslave the entire human population within the machinations of Empire. As human bodies and minds become more thoroughly enmeshed in the bionetworks, surveillance, data collection, augmented realities, cyborg hybridizations, and genetic transformations wrought by the aliens, the global masses all become subject to imperial desire and power. Thus, I assert, Thompson configures the connective technologies of contemporary globalization as overt tools of colonialism: the networked subjectivities of surveillance capitalism are steeped in Black experiences of slavery and the colonial gaze, metastasizing the racist logic of imperialism through the mechanisms of Empire to encompass the whole planet. Thus the Wormwood narrative posits that Black experiences are always already implied by the imperialist resonances of the science fiction genre, highlighted here as foundational for everyone else to recognize their own relationship to the technologies of global capitalism—to see that we all inhabit a planet that already turned Black.